Analyzing Green Building of Appropriate Site Development Requirements in High Rise Building - Rezi Berliana Yasinta; Muhammad Aldino Pradana; Dahlia Dahlia (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2024)
Increasingly severe global warming encourages society to reduce greenhouse gas emissions. A crucial element of this approach involves embracing Green Building concepts, ensuring each construction phase adheres to environmentally responsible practices. One of the aspects is Appropriate Site Development (ASD), requiring consideration of green-oriented factors such as site selection criteria, community accessibility, public transportation, bicycle facilities, macroclimate, and rain-runoff water management. A case study at the Faculty of Engineering, State University of Jakarta, identified deficiencies like the absence of bicycle parking, insufficient public toilet facilities, and distant bus stops. This study analyzes ASD green building criteria and identifies applicable land use standards at the Faculty of Engineering, UNJ. The research entails two stages, such as a literature review and a rating system based on Green Building Certification Institute (GBCI). The results showed significant progress from the Faculty of Engineering UNJ, by obtaining 11 points out of a maximum 16 points in the ASD aspect. This case only implemented 2 indicators, namely Heat Island Effect and Storm Water Management. This analysis focused exclusively on ASD criteria without pursuing GBCI certification.